Who Successfully Quits Smoking in Indonesia? A Survival Analysis of GATS 2021 - Sadarang, Rimawati Aulia Insani (Unihealth Community Research, 2025)
Tobacco use is a major health burden in Indonesia, especially among men, while the use of cessation aids remains low. Although more individuals are attempting to quit, factors influencing successful cessation are not fully understood. This cross-sectional study analyzed data from the 2021 Global Adult Tobacco Survey (GATS) Indonesia. A total of 1,111 respondents aged ≥15 years who had ever smoked were included. Kaplan-Meier survival curves and Cox proportional hazard models assessed demographic and behavioral predictors of smoking cessation. Among respondents, 68.9% had quit smoking for at least 12 months. Women were more likely to quit than men (aHR = 4.23; 95% CI: 2.64–6.75). Education level was positively associated with cessation: medium (aHR = 1.79) and high (aHR = 2.17) education levels had higher quit rates than low education. Only students showed significantly higher cessation rates among employment groups (aHR = 6.19). Exposure to e-cigarettes was linked to lower cessation likelihood, although frequency of use was not significant. Female gender and higher education are key factors in successful smoking cessation. Programs should address social disparities and offer targeted support for less-educated and socially disadvantaged populations.